Lawyers' language : how and why legal language is different - Phillips, Alfred (Routledge, 2003)
"The law presumes that everyone knows the law, yet the obscurity of lawyers' language puts it out of reach of those who are presumed to know it." "The aim of this book is to establish that, on the contrary, the development and maintenance of the law's special language can be justified. The notion of representation is applied to the relationship between legal language and ordinary language. In a judge's use of a language designed to build a coherent and internally consistent body of applied law, which will stand in a relationship of representation to ordinary language, the judge can properly be said to be the people's representative." "Cases are used throughout the book to underpin the author's argument. Lawyers' Language justifies the transformation of ordinary language into a special discourse for the purposes of the legal system."--Jacket